Joint development by the regents institutions of programs in sustainability management: a panel discussion - Hutchinson, Stacy L.; Meyers, Keith; Reinert, Dana; Crawford, Chris; White, Stacey Swearingen; Maes, Sue C. (Kansas State University, 2011)
During this session, a panel will discuss the prospects of jointly developing degree or certificate programs in sustainability management by the Kansas Regents Institutions, including four-year universities, community colleges and technical schools. They will review the need for such programs in Kansas and examine what resources are currently available or would be required to establish a partnership among the institutions to develop the degree or certificate programs. The panel will also review similar programs offered by other institutions. The panel will consist of five or six members representing Kansas State University, University of Kansas, Kansas community colleges and technical schools, the Kansas Dept. of Commerce, and the coordinator of the Kansas Energy Network of Education and Training (Energy NET), a joint program of the Board of Regents and Dept. of Commerce.
Keywords: Degree programs; Sustainability management; Kansas